Intravitreal bevacizumab plus propranolol for neovascular age-related macular degeneration (the BEVALOL study): a phase I clinical trial - José Edísio da Silva Tavares Neto; Francyne Veiga Reis Cyrino; Moises Moura Lucena; Ingrid U. Scott; André Márcio Vieira Messias; Rodrigo Jorge (International Journal of Retina and Vitreous, 2023)
Abstract Background Given the persistently large public health impact of neovascular age-related macular degeneration (nARMD) despite many years of anti-VEGF therapy as the first-line treatment and the demonstrated ability of b-blockers to reduce neovascularization, a synergistic effect between an anti-VEGF agent and an intravitreal beta-blocker is important to investigate in the quest for therapeutic alternatives that maximize efficacy and/or reduce costs. The main purpose of this study is to investigate the safety of a 0.1 ml intravitreal injection of a combination of bevacizumab (1.25 mg/0.05 ml) and propranolol (50 g/0.05 ml) to treat nARMD. Methods Prospective phase I clinical trial that included patients with nARMD. Comprehensive ophthalmic evaluation was performed at baseline and included Early Treatment Diabetic Retinopathy Study (ETDRS) best-corrected visual acuity (BCVA), biomicroscopy of the anterior and posterior segments, binocular indirect ophthalmoscopy, color fundus photography, spectral domain optical coherence tomography (OCT), OCT angiography (OCT-A), fluorescein angiography (Spectralis, Heidelberg), and full-field electroretinography (ERG). All eyes were treated with a 0.1 ml intravitreal injection of a combination of bevacizumab (1.25 mg/0.05 ml) and propranolol (50 g/0.05 ml) within 1 week of baseline evaluation. The patients were reexamined at weeks 4, 8 and 12, and clinical evaluation and SD-OCT were performed at all follow-up visits. Additional injections of combination bevacizumab (1.25 mg/0.05 ml) and propranolol (50 g/0.05 ml) were administered at weeks 4 and 8. At the final study evaluation (week 12), color fundus photography, OCT-A, fluorescein angiography, and full-field ERG were repeated. Results Eleven patients (11 eyes) completed all study visits of the 12 week study. Full field ERG b-waves did not show significant (p < 0.05) changes at week 12 compared to baseline. During the 12 week follow-up period, none of the study eyes developed intraocular inflammation, endophthalmitis or intraocular pressure elevation more than 4 mmHg over baseline. Mean ± SE BCVA (logMAR) was 0.79 ± 0.09 at baseline and was significantly (p < 0.05) improved to 0.61 ± 0.10 at week 4; 0.53 ± 0.10 at week 8; and 0.51 ± 0.09 at week 12. Mean ± SE central subfield thickness (CST) (μm) was 462 ± 45 at baseline and was significantly (p < 0.05) lower at 4, 8 and 12 weeks (385 ± 37; 356 ± 29 and 341 ± 24, respectively). Conclusions In this 12 week trial of a combination of intravitreal bevacizumab and propranolol for treatment of nARMD, no adverse events or signals of ocular toxicity were observed. Further studies using this combination therapy are warranted. Trial Registration Project registered in Plataforma Brasil with CAAE number 28108920.0.0000.5440 and approved in ethics committee of Clinics Hospital of Ribeirao Preto Medicine School of São Paulo University—Ribeirão Preto, São Paulo, Brazil (appreciation number 3.999.989 gave the approval).